The role of a 2-on-2 haemoglobin in oxidative and nitrosative stress resistance of Antarctic Pseudoalteromonas haloplanktis TAC125. - PARRILLI, ERMENEGILDA; GIULIANI, MARIA; MARINO, GENNARO; TUTINO, MARIA LUISA; Giordano D.; Russo R.; Verde C (2010)
The 2-on-2 haemoglobins, previously named truncated, are monomeric, low molecular weight oxygen-binding proteins that share the overall topology with vertebrate haemoglobins. Although several studies on 2-on-2 haemoglobins have been reported, their physiological and biochemical functions are not yet well defined, and various roles have been suggested. The genome of the psychrophilic Antarctic marine bacterium Pseudoalteromonas haloplanktis TAC125 (PhTAC125) is endowed with three genes encoding 2-on-2 haemoglobins. To investigate the function played by one of the three trHbs, PhHbO, a PhTAC125 genomic mutant strain was constructed, in which the encoding gene was knocked out. The mutant strain was grown under controlled conditions and several aspects of bacterium physiology were compared with those of wild-type cells when dissolved oxygen pressure in solution and growth temperature were changed. Interestingly, inactivation of the PhHbO encoding gene makes the mutant bacterial strain sensitive to high solution oxygen pressure , to H2O2, and to a nitrosating agent, suggesting the involvement of PhHbO in oxidative and nitrosative stress resistance.